Cytotoxic Activity of Nisin on Human Cancer Cell Lines: A Systematic Review - Hosseini , Sareh Sadat; Hajikhani , Bahareh; Goudarzi , Hossein; Rommasi, Foad; Nasiri , Mohammad Javad (Novelty in Biomedicine, 2022)
Cancer is one of the leading causes of mortality and morbidity worldwide. Nisin consists of various and uncommon amino acids as an antimicrobial protein synthesized by the Lactobacilli genus. The current systematic review aimed to evaluate the anticancer activity of Nisin, an antibacterial peptide, on different human cancer cell lines. We searched PubMed/Medline and Embase databases to detect the studies addressing the cytotoxic activity of Nisin on human cancer cell lines. Our study was conducted following the "PRISMA" guideline. Of 202 potentially relevant articles, 15 studies met the inclusion criteria and were included for further analysis. The results revealed that Nisin has different levels of anticancer activity on human cancer cell lines. The outcomes of our review indicate that some cancer cell lines, such as cell skin carcinoma (A431), Melanoma cells (A375), and colorectal cancer cell lines (LS180), are strongly affected by the anticancer properties of Nisin. In contrast, the anticancer effect of Nisin on others like Human promyelocytic leukemia (HL60) is lower. Nisin shows significant anticancer effects in different cancer cell lines. Utilizing Nisin simultaneously with other antitumor agents can enhance its anticancer features and efficacy. Further studies, especially in vivo assay and clinical trials, are recommended to achieve more accurate results in this field.